Spiritual Growth and Mental Health Gains: Benefits of Awakened Awareness for U.S. College Students at Three-Month Follow-Up - Abigail Crete; Suza C. Scalora; Elisabeth J. Mistur; Micheline Anderson; Lisa Miller (Religions, 2025)
Previous research has documented broad benefits of spiritual intervention programs, including improved spirituality and ameliorated mental health symptoms. However, long-term follow-up examinations of such interventions have yet to be conducted. This study reports on changes in psychological and spiritual variables from posttest to 3-month follow-up in a sample of U.S. undergraduate students. N = 84 undergraduate students ages 18–25 (M = 19.75, SD = 1.6; 69 female, 11 male, and 4 nonbinary) received Awakened Awareness for Adolescents (AA-As), a spirit–mind–body (SMB) intervention composed of 8 weekly 90-min sessions, and completed measures of spirituality (spirituality, spiritual growth, spiritual decline, and Awakened Awareness) and mental health (depression, anxiety, and posttraumatic stress) at posttest and again at 3-month follow-up. Paired-sample t-tests revealed maintenance of spiritual improvements (Awakened Awareness, spiritual growth, and relational spirituality with the Higher Power) with the exception of reversal of spiritual decline and significant ongoing improvements in clinical measures in the months following posttest. Additionally, we observed a moderating effect such that changes in spiritual decline after posttest were associated with follow-up posttraumatic stress. An ongoing lived transcendent relationship with the Higher Power, Awakened Awareness, and spiritual growth appears to offer sustained protection at three-month follow-up against depression and symptoms of trauma. Our findings support the efficacy of AA-A as well as the need for ongoing SMB wellness resources.